2020
DOI: 10.35848/1882-0786/abbfde
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of deep-sub-micrometer NbN/AlN/NbN epitaxial junctions on a Si-substrate

Abstract: We have developed a novel fabrication process for ultra-small, full-epitaxial NbN Josephson junctions on a silicon (Si) substrate. A full-epitaxial NbN/AlN/NbN tri-layer was grown on a Si (100) wafer with a (200)-oriented TiN buffer layer. It was patterned into Josephson junctions by an electron beam lithography (EBL) for junction definition followed by a reactive ion etch (RIE). A chemical mechanical polishing (CMP) process and an additional RIE by using CHF3 gas formed reliable electrical contacts between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…From measurements of the current-voltage characteristics of test JJs fabricated on the same wafer as the qubits at 4., the Josephson critical current density 𝐽𝐽 𝑐𝑐 , was found to be 40 -48 A/cm 2 . Additionally, we confirmed that there is no change in 𝐽𝐽 𝑐𝑐 between before and after BHF etching of the SiO2 layer, indicating no damage in the JJs by BHF treatment36 .Device parameters. The fabricated qubit-resonator architecture is depicted in Fig.1.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…From measurements of the current-voltage characteristics of test JJs fabricated on the same wafer as the qubits at 4., the Josephson critical current density 𝐽𝐽 𝑐𝑐 , was found to be 40 -48 A/cm 2 . Additionally, we confirmed that there is no change in 𝐽𝐽 𝑐𝑐 between before and after BHF etching of the SiO2 layer, indicating no damage in the JJs by BHF treatment36 .Device parameters. The fabricated qubit-resonator architecture is depicted in Fig.1.…”
supporting
confidence: 67%
“…Fabrication of all-nitride superconducting qubit. Samples were fabricated by using epitaxial growth of NbN/AlN/NbN junctions on Si wafers with TiN buffers and planarization by CMP 27,36 . In brief the fabrication flow is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Optimizing Models The structure of the atoms was optimized by using DFT based on the projector augmented wave (PAW) method. During relaxation, the Vienna Ab-initio Simulation Package (VASP) [ 21 , 28 , 40 ] was used for calculation. Perdew–Burke–Ernzerhof (PBE) [ 41 ] was used for the exchange–correlation functional between electrons.…”
Section: Appendix A1 System Modelsmentioning
confidence: 99%
“…To date, good experimental results have been achieved by optimizing the substrates and process conditions [ 9 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For example, through increasing the buffer layers between the junction and the substrate to reduce the dielectric loss, the energy relaxation time T1 of the all-nitride junctions reaches 16 microseconds (ms), and the phase relaxation time T2 reaches 22 ms [ 13 , 21 ]. However, the results still fall short of expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting materials grown on Si or Al 2 O 3 substrates may form films of high crystallinity and with inherently low dielectric loss, thus are explored as the materials for building superconducting quantum circuits 1 6 . Recently, researchers have made efforts to search for new superconducting films with stable superconducting properties and mature processing used in the quantum computing field, aiming to improve the performance of superconducting qubits, including long coherence time and fast gates 5 , 7 12 .…”
Section: Introductionmentioning
confidence: 99%